ETIKA KEPEMIMPINAN ISLAM DI TENGAH KONTESTASI MORAL: STUDI KASUS GUS MIFTAH DALAM PERSPEKTIF AL-QUR’AN - Muhammad Pajri Zullian; Devina Novela; Aisyah Nur; Saifullah (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2025)
The phenomenon of ethical leadership in Islam has become increasingly crucial amid contemporary social dynamics. This study aims to analyze the principles of ethical leadership from the perspective of the Qur'an and their application in the case of Gus Miftah. A descriptive qualitative approach based on library research was employed. Primary sources include the Qur'an, Tafsir al-Azhar by Hamka, and Al-Ahkam As-Sultaniyyah. The data were analyzed using content analysis through a deductive approach—deriving general principles from primary texts to examine contemporary leadership phenomena. The findings reveal that ethical leadership in Islam is grounded in the values of trustworthiness (amanah), justice, consultation (shura), and etiquette in speech. In the case of Gus Miftah, a discrepancy is found between the ideal Qur'anic leadership principles and the public communication practices exhibited, particularly concerning respect for individual dignity. Theoretically, this study contributes to the development of Qur'anic-based ethical leadership frameworks within contemporary exegesis. Practically, it offers insights for religious figures and public leaders to enhance ethical sensitivity and communication standards in social and religious spheres.